Negative thermal expansion in YbMn2Ge2 induced by the dual effect of magnetism and valence transition - Yongqiang Qiao (Nature Portfolio, 2021)
Abstract Negative thermal expansion (NTE) is an intriguing property, which is generally triggered by a single NTE mechanism. In this work, an enhanced NTE (α v  = −32.9 × 10−6 K−1, ΔT = 175 K) is achieved in YbMn2Ge2 intermetallic compound to be caused by a dual effect of magnetism and valence transition. In YbMn2Ge2, the Mn sublattice that forms the antiferromagnetic structure induces the magnetovolume effect, which contributes to the NTE below the Néel temperature (525 K). Concomitantly, the valence state of Yb increases from 2.40 to 2.82 in the temperature range of 300–700 K, which simultaneously causes the contraction of the unit cell volume due to smaller volume of Yb3+ than that of Yb2+. As a result, such combined effect gives rise to an enhanced NTE. The present study not only sheds light on the peculiar NTE mechanism of YbMn2Ge2, but also indicates the dual effect as a possible promising method to produce enhanced NTE materials.